Analisis statis model fuselage berlubang dengan penguat grid material metal menggunakan metode elemen hingga - Hasana, Muhamad Irfan; Sudirab, I Gusti Ngurah; Herlina (BKS-TM Indonesia, 2023)
In addition to the material on the aircraft, structural configuration is also important. One of the structural configurations that can distribute loads and moments evenly is the grid structure. In an aeroplane, there are holes in the structure, which is unavoidable because it has an important, one of which is a window hole. This study analyzes the fuselage model with a grid structure of variations in the thickness of the frame on the window against deformation, stress, and margin of safety under static loading. The analysis was performed by applying a bending load and a torsion load of 10,000 N, and the boundary conditions were assumed to be a cantilever beam. Static calculation analysis using the finite element method (FEM) with MSC. Patran/Nastran software. The research results found that the existence of holes causes the maximum deformation and maximum stress values to increase, but the mass in the structure decreases. In addition, the increase in the window frame's thickness affects the maximum deformation and maximum stress values, which decrease, but the structure's mass increases. In addition, based on the decreasing maximum stress value, the MOS value increases. The margin of safety value in all structural models is said to be safe because the margin of safety value is greater than 0 (MOS > 0). The results of this study show that the grid structure is stiffer and stronger than conventional structures because it has lower deformation va- lues and maximum stress.